2013
DOI: 10.1016/j.scitotenv.2012.10.072
|View full text |Cite
|
Sign up to set email alerts
|

The Near-Road Exposures and Effects of Urban Air Pollutants Study (NEXUS): Study design and methods

Abstract: The Near-Road Exposures and Effects of Urban Air Pollutants Study (NEXUS) was designed to examine the relationship between near-roadway exposures to air pollutants and respiratory outcomes in a cohort of asthmatic children who live close to major roadways in Detroit, Michigan USA. From September 2010 to December 2012 a total of 139 children with asthma, ages 6–14, were enrolled in the study on the basis of the proximity of their home to major roadways that carried different amounts of diesel traffic. The goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 53 publications
2
65
0
Order By: Relevance
“…The STOK technique is implemented with BMElib (Bayesian Maximization Entropy library) (Serre, 1999). A detailed description of the STOK algorithm, which was developed and applied for the Near-road Exposures to Urban Air Pollutants Study (NEXUS) (Vette et al, 2013) in Detroit, MI, can be found in Arunachalam et al (2014). We applied this algorithm from Arunachalam et al (2014) to estimate hourly background concentrations at all receptors in each of the study domains.…”
Section: Background Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The STOK technique is implemented with BMElib (Bayesian Maximization Entropy library) (Serre, 1999). A detailed description of the STOK algorithm, which was developed and applied for the Near-road Exposures to Urban Air Pollutants Study (NEXUS) (Vette et al, 2013) in Detroit, MI, can be found in Arunachalam et al (2014). We applied this algorithm from Arunachalam et al (2014) to estimate hourly background concentrations at all receptors in each of the study domains.…”
Section: Background Concentrationsmentioning
confidence: 99%
“…Accurate characterization of exposure to air pollution from traffic is also important for environmental epidemiologic studies (Lobdell et al, 2011;Vette et al, 2013). However, estimating near-road exposure is challenging because of dynamic traffic conditions, multiple pollutants, the need to separate near-road and regional pollution, and the spatial and temporal resolution needed to document pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 To reduce exposure misclassification, we are developing an air pollution exposure model for individuals (EMI) in health studies. 4-6 The EMI predicts personal exposures based on outdoor concentrations, meteorology, questionnaire information (e.g., building characteristics, occupant behavior related to building operation and indoor sources), and time-location information. This study describes a critical aspect of EMI: the development and evaluation of a classification model, called MicroTrac, that estimates time of day and duration spent by individuals in eight ME (indoors and outdoors at home, work, school; inside vehicles; other locations) based on global positioning system (GPS) data and geocoded (geographic coordinates expressed as latitude and longitude) boundaries of buildings.…”
Section: Introductionmentioning
confidence: 99%
“…11 For individual exposure assessments, diaries from the study participants can be used. 4,12,13 However, diaries have limitations, including burden on participants, inaccuracies due to recall and reporting errors, and missing data.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges associated with including commute-time exposure and indoor resident-specific sources are widely acknowledged and improvements are ongoing (Dias and Tchepel 2014;Vette et al 2013). Exposure while commuting is currently best handled by in-traffic exposure models (Dons et al 2014a) or LUR models that include traffic volumes/road source intensity.…”
Section: Study Limitations and Recommendationsmentioning
confidence: 99%